Democratizing Science The Political Roots of the Public Engagement Agenda - Mattei, Paola (Bristol University Press, 2023)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. This book examines potential remedies for improving public trust and the legitimacy of science. It reviews different policy approaches adopted by governments to incentivise the empowerment of stakeholders through co-production arrangements, participatory mechanisms, public engagement and interaction between citizens and researchers. Offering an original analysis of the political roots of the governmental impact and engagement agenda, this book sheds much-needed light on the wider connections to democracy.